Method for measuring voltages in channels of a hemispherical resonator gyroscope with an arbitrary orientation axes - Igor Parkhomey; Juliy Boiko; Irina Zeniv; Taras Bondarenko (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The article deals with issues related to solid wave gyroscopes, which are used as a sensor in inertial navigation systems. The article considers a variant of solving problem, when oscillations of the resonator are excited in directions that coincide with their own axes, oriented a priori is unknown. The main contribution this article is the method is proposed for measuring signal amplitudes in virtual main and quadrature channels, the orientation of which does not coincide with the orientation of the signal pickup electrodes. This is achieved by modeling algorithms for measuring the slope of the resonator's own axes and signal amplitudes in virtual channels are evaluation. In order to verify the adequacy of the proposed models simplified calculation formulas for programming microcontrollers are presented. An estimate of the error due to the use of simplified formulas is made. It is assumed that the use of this method will reduce the requirements for the quality of balancing the resonators of gyroscopes. The findings will be useful for mass production of navigation systems with gyroscopes, which have a small drift and are capable of experiencing large shock linear accelerations, for example, in underground inclined drilling, and in meteorological rockets.